SUPLAI NITROGEN TERHADAP PERTUMBUHAN, HASIL, KADAR GULA TOTAL KUBIS BUNGA (Brassica oleraeea sp .) DAN RESIDU NITROGEN MINERAL DI DALAM TANAH - Andina Mayangsari (AGRIBIOS, 2012)
This study titled nitrogen supply on growth, yield, total sugar content of cabbage flowers (Brassica oleraeea sp.) and residual mineral Nitrogen in the soil. This research is done in the village os Sumber Jeruk Kalisat, Jember district from 2 April 2008 - 30 June 2008, where the altitude is 200 m above sea level. Cabbage flowers is used by white snow variety 50 (age harvest the day after harvest 50). The design is used by Randomized Block Design (RBD) 6 treatment supply Nitrogen (N) with 4 replications. Nitrogen supply supply treatment are N1 (100 kg N/ Ha), N2 (150 Ha), N3 (200 kg/ H), N4 (250 kg/ Ha), N5 (300 kg N/Ha), N6 (350 kg N/Ha).Parameters of study include : Plant height (cm), stem diameter (cm), leaf number, leaf length (cm), leaf width (cm), leaf area (cm), weight of fresh flowers and stover (g), dry weight of flowers and stover (g), flower diameter (cm), total sugar content of interest and available soil N residues after harvest. These result indicate Nitrogen supply of vegetative growth was not significantly different, except for plant height at harvest (the day after harvest 45) and the weight of stover. The highest result achieved by treatment of N supply of 200 kg/ Ha N rate and stover weight to 45.12 tons / Ha. Supply nitrogen to the total sugar content were not significantly different. Nitrogen supply to the different residual N in the soil is very real.